2018
DOI: 10.1044/2018_jslhr-l-17-0064
|View full text |Cite
|
Sign up to set email alerts
|

A Duck Wearing Boots?! Pragmatic Language Strategies for Repairing Communication Breakdowns Across Genetically Based Neurodevelopmental Disabilities

Abstract: All groups showed some proficiency in repairing communication breakdowns, although individuals with ASD-O and FXS-ASD demonstrated some key areas of difficulty, highlighting the importance of considering ASD symptomatology in assessment and treatment of males with FXS. Findings also suggest that, across groups, multiple requests for clarification may lead to disengagement from the interaction. Finally, correlated skills observed across groups could implicate different underlying skills related to communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
(118 reference statements)
2
11
0
Order By: Relevance
“…Because data came from a larger longitudinal study in which multiple ADOSs were usually available for a given child (i.e., 29% had one ADOS, 54% had two, 15% had three, and 2% had four), calibrated autism severity scores based on the ADOS (Gotham, Pickles, & Lord, 2009) were averaged across multiple ADOSs when available to determine ASD status (see Table 1 for average severity scores). The utilization of longitudinal ADOS assessments is consistent with our prior work (i.e., Barstein, Martin, Lee, & Losh, 2018;Klusek et al, 2014a; and deemed to be the best estimate of, and most valid approach to, determining ASD status using these longitudinal data. Staff members administering and scoring the ADOS achieved reliability either through direct training with the test developers or through intralab reliability per standards outlined by the test developers.…”
Section: Asd Classificationsupporting
confidence: 74%
“…Because data came from a larger longitudinal study in which multiple ADOSs were usually available for a given child (i.e., 29% had one ADOS, 54% had two, 15% had three, and 2% had four), calibrated autism severity scores based on the ADOS (Gotham, Pickles, & Lord, 2009) were averaged across multiple ADOSs when available to determine ASD status (see Table 1 for average severity scores). The utilization of longitudinal ADOS assessments is consistent with our prior work (i.e., Barstein, Martin, Lee, & Losh, 2018;Klusek et al, 2014a; and deemed to be the best estimate of, and most valid approach to, determining ASD status using these longitudinal data. Staff members administering and scoring the ADOS achieved reliability either through direct training with the test developers or through intralab reliability per standards outlined by the test developers.…”
Section: Asd Classificationsupporting
confidence: 74%
“…In general, pragmatic language delays are often noted in individuals with DS, particularly relative to expectations based on nonverbal cognition [26,[35][36][37][38]. That said, pragmatic strengths are often observed in DS, when compared to individuals with other neurodevelopmental disorders [8,39,40]. Sensory and motor impairments, as well as cognitive functioning (e.g., nonverbal MA), have been found to contribute to the expressive language problems of individuals with DS; however, these factors account for a relatively small proportion of the variance in expressive language outcomes [21,23,[29][30][31][32][33][34]36], suggesting a need for research to identify additional factors.…”
Section: Expressive Language Development In Individuals With Dsmentioning
confidence: 99%
“…Repair and CARS scores were not significantly correlated, suggesting that the relationship identified in our prediction models may be due to Type I error. Perhaps this area of pragmatics is unaffected by the presence of autism symptoms in FXS, as previous studies have demonstrated that children and adolescents with FXS and autism have robust ability to repair (Barstein et al., 2018). Additionally, children with autism in the one-word stage repair 85% of the time, suggesting repair may not be reliant on expressive language skills in children with autism (Keen, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Repair has been suggested as an area of specific deficits in males with FXS with co-morbid autism (Barstein et al., 2018). Our multilevel regression models suggested that increased average autism symptomology was related to increased probability of repair.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation